History in the plural : an introduction to the work of Reinhart Koselleck - Olsen, Niklas, 1975- (Berghahn Books, 2012)
Reinhart Koselleck (1923-2006) was one of most imposing and influential European intellectual historians in the twentieth century. Constantly probing and transgressing the boundaries of mainstream historical writing, he created numerous highly innovative approaches, absorbing influences from other academic disciplines as represented in the work of philosophers and political thinkers like Hans Georg Gadamer and Carl Schmitt and that of internationally renowned scholars such as Hayden White, Michel Foucault, and Quentin Skinner. An advocate of "grand theory," Koselleck was an inspiration to many.